Memahami Keheningan sebagai Persiapan Batin Umat dalam Mengikuti Perayaan Ekaristi - Bartolomeus Sihite; Evimawati Harefa; Irmina Mitrang Fani Waruwu (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
In the celebration of the Eucharist, silence is an important element in liturgical celebrations. Liturgical silence is a means that sends people into the inner world where God is personally experienced. Silence is a time when people listen and absorb God's Word and bear fruit in their daily lives through words, actions and deeds. The author's purpose in making this scientific paper is to urge the people to maintain silence while participating in the Eucharistic Celebration, so that all people can prepare themselves and mind to follow and carry out the Eucharistic Celebration with a calm heart and mind. The method of writing this thesis is a literature review. This scientific work was compiled based on the author's concern about the lack of appreciation of the people in participating in the Eucharistic Celebration. It is undeniable that there are things that disturb the silence during the Eucharistic Celebration, such as the noise in the sacrament when the officers are preparing themselves, and the sound of mobile phones ringing. Therefore, before the Eucharistic Celebration, it is highly recommended that silence can be created, both in the church and in the area around the church. This paper recalls that silence can be created through prayer. And the most important thing in prayer is not to first seek what we want, but to be aware of the desire and inner movement that is driven by God Himself.